Will the Future Economics Teacher Be Prepared to Be up against Industrial Revolution 4.0? - Febrianto , Indra; Inayati, Ro’ufah (KnE Social Sciences, 2020)
Today the Industrial Revolution has reached its peak where technology is the basis of human life. The Indonesian government has launched Making Indonesia 4.0 that grown massively. One sector that must be prepared in achieving Making Indonesia is the Education Sector which can be done by improving the human resources The readiness of Future Economics Teachers spearheaded the improvement of human resources quality. Therefore, it is necessary to conduct research that focuses on analyzing the readiness of Future Economics Teachers to face the Industrial Revolution 4.0. This study uses descriptive qualitative methods with a type of case study research. Primary data obtained from in-depth interview together with respondents and secondary data obtained from the document that shows the result of educational subject. Data collection is done by the method of observation, interview, and documentation that using source triangulation and method triangulation. The indicators used to analyze the readiness of these Future Economics Teachers are (1) Educational Competence, (2) Competence for Technological Commercialization, (3) Competence of Globalization, (4) Competence in the Future Strategies, and (5) Conselor Competence Based on the results of this study, it can be concluded that; (1) Educational Competence possessed by Future Economics Teacher from the two ex-IKIP state university in East Java is sufficiently capable in dealing with the Industrial Revolution 4.0; (2) Competence for Technological Commercialization of the Future Economics Teachers is not too good to face the Industrial Revolution 4.0; (3) Competence of Globalization that is owned cannot be maximized in facing the Industrial Revolution 4.0;(4) Competence in the Future Strategy shows that this Future Economics Teacher does not have a definite strategy to predict what will happen in the Industrial Revolution 4.0; and (5) Conselor Competence shows good but still not enough to face the Industrial Revolution 4.0. Keywords: Education Sector, Ex-IKIP State University, The Industrial Revolution 4.0, The Readiness of Future Economics Teachers.